Experimental study of tower noise on the basis of blade-tower interaction - Yu, Hailong; Li, Zhichuan; Guo, Qi; Qi, Lei; Li, Ning; Zhu, Kuixing; Wang, Peng; Sun, Ke (Frontiers in Energy Research, 2024)
Blade-tower interaction(BTI) noise from offshore wind turbines has a negative impact on marine organisms, so further research is needed on the sound generation mechanism of blade-tower noise. Wind tunnel experiments are conducted to collect velocity distribution, Reynolds shear stress, and turbulence kinetic energy data in the vertical incoming flow direction plane behind the tower during the wind turbine impeller-tower interference. The hot wire anemometer velocity method is used to obtain these data. Finally, the flow above characteristics are combined to elucidate the underlying causes of aerodynamic noise in the near wake of the tower resulting from blade-tower interference. The results demonstrate that the blade's passing effect causes irregular velocity distribution and vortex migration and mixing in the near wake of the tower, resulting in the most significant difference in Reynolds shear stress at the 0.71R position of the blade during the blade's transition from an azimuthal angle of 180°to 210°(upward). Furthermore, a strong correlation was identified between the peak turbulent kinetic energy and the peak acoustic pressure value measured during the rotational cycle when the blade ran up to 210 °azimuth angle. Therefore, it is deduced that the aerodynamic noise at the rear of the tower is attributed to the increase in momentum exchange caused by fluid doping and bursting, which are driven by Reynolds shear stress. Momentum exchange induces an increase in turbulent kinetic energy, which results in fluid velocity pulsations, pressure pulsations, and, thus, noise. The reduction in fluid mixing and the reduction in pressure pulsation subsequently lead to a reduction in the noise generated by the tower. Therefore, a viable approach to reducing BTI noise involves minimizing momentum exchange.